A low energy process for the recovery of bioproducts from cyanobacteria using a ball mill - Steve Skill (Biochemical Engineering Journal, 2012)
Efficient and economical large scale bioprocessing of microalgae to produce a range of bio-products, working towards a biorefinery approach, is critical for the success of algal industrial biotechnology. The key process variables that affect the recovery of products from different sub-cellular locations were investigated using a high throughput cell disruption system and a cyanobacterium as model organism. This information was then used to design and test a differential recovery procedure at pilot scale using a custom designed ball mill that consumed 1.87. kWh/kg of dry biomass used approximately 34% lower than the best algal disruption system reported. The balance between the number of collisions and force of each collision between grinding media and the microorganism were manipulated to achieve differential recovery. Greater than 99 and 95% solids were recovered at the end of first and second ball milling step respectively through gravity sedimentation, an energy efficient solid-liquid separation technique. Based on these results and the release rates of intracellular and/or extracellular products tested, a theoretical framework is presented for the design of a differential recovery process using ball mills.